2021
DOI: 10.1108/jica-03-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and integrated care: an application of integrated care knowledge to understanding services for wicked issues

Abstract: PurposePeople experiencing homelessness often have complex needs requiring a range of support. These may include health problems (physical illness, mental health and/or substance misuse) as well as social, financial and housing needs. Addressing these issues requires a high degree of coordination amongst services. It is, thus, an example of a wicked policy issue. The purpose of this paper is to examine the challenge of integrating care in this context using evidence from an evaluation of English hospital disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Homelessness has well‐documented negative impacts on health and is associated with high levels of chronic and acute disease, mortality, and cyclical acute care hospital utilization (Gryczynski et al., 2020; Morrison, 2009). Integrating healthcare delivery at shelters has been shown to improve both access to healthcare and clinical outcomes for people experiencing homelessness through directly addressing physical and mental health needs with on‐site medical assistance and coordinated referral to outside services (Clark et al., 2021; Cornes et al., 2018). People with integrated care and permanent housing use emergency departments less often and experience shorter hospital stays (Sadowski et al., 2009; Salhi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Homelessness has well‐documented negative impacts on health and is associated with high levels of chronic and acute disease, mortality, and cyclical acute care hospital utilization (Gryczynski et al., 2020; Morrison, 2009). Integrating healthcare delivery at shelters has been shown to improve both access to healthcare and clinical outcomes for people experiencing homelessness through directly addressing physical and mental health needs with on‐site medical assistance and coordinated referral to outside services (Clark et al., 2021; Cornes et al., 2018). People with integrated care and permanent housing use emergency departments less often and experience shorter hospital stays (Sadowski et al., 2009; Salhi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research identified that IH education is needed to address inequalities and manage the multiple needs of IH groups (Clark et al, 2022;Davis and Lovegrove, 2015). However, there has been little progress or research to understand what educational interventions should look like or how they can promote interprofessional care.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research identified that IH education is needed to address inequalities and manage the multiple needs of IH groups (Clark et al. , 2022; Davis and Lovegrove, 2015).…”
Section: Introductionmentioning
confidence: 99%